2012
DOI: 10.1242/jcs.108209
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CD23 as a functional receptor for the proinflammatory cytokine AIMP1/p43

Abstract: SummaryAminoacyl-tRNA-synthetase-interacting multifunctional protein 1 (AIMP1/p43) can be secreted to trigger proinflammatory molecules while it is predominantly bound to a cytoplasmic macromolecular protein complex that contains several different aminoacyl-tRNA synthetases. Although its activities as a secreted signaling factor have been well characterized, the functional receptor for its proinflammatory activity has not yet identified. In this study, we have identified the receptor molecule for AIMP1 that me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 34 publications
1
15
0
1
Order By: Relevance
“…3E). This result suggests that the association of 15B3AF IgG with P2 region of AIMP1 is critical for blocking AIMP1-mediated TNFa secretion, in agreement with finding that the region between aa 101-192 in AIMP1 is critical for TNFa production [28]. Because AIMP1 induces the secretion of inflammatory cytokines via the activation of ERK and NFkB [19], we examined whether 15B3AF IgG could inhibit the AIMP1-mediated activation of ERK and NFkB in THP-1 monocytes.…”
Section: Aimp1 Neutralizing Antibody Inhibits Aimp1 Cytokine Activitysupporting
confidence: 80%
See 1 more Smart Citation
“…3E). This result suggests that the association of 15B3AF IgG with P2 region of AIMP1 is critical for blocking AIMP1-mediated TNFa secretion, in agreement with finding that the region between aa 101-192 in AIMP1 is critical for TNFa production [28]. Because AIMP1 induces the secretion of inflammatory cytokines via the activation of ERK and NFkB [19], we examined whether 15B3AF IgG could inhibit the AIMP1-mediated activation of ERK and NFkB in THP-1 monocytes.…”
Section: Aimp1 Neutralizing Antibody Inhibits Aimp1 Cytokine Activitysupporting
confidence: 80%
“…2A). Recently, CD23, a low affinity receptor for IgE, was isolated as a receptor for AIMP1 that induces the secretion of TNFa from monocytes and peripheral blood mononuclear cells [28]. CD23 regulates immune cell activation, and its expression is increased in RA [29,30].…”
Section: Aimp1 Promotes Osteoclastogenesismentioning
confidence: 99%
“…Recently, CD23, a known receptor for IgE, was identified as a receptor for secreted AIMP1 [136]. This study showed that downregulation of CD23 reduced the activation of ERK1/2 and AIMP1-dependent cytokine secretion in primary human monocytes.…”
Section: Ars-interacting Multi-functional Proteinsmentioning
confidence: 83%
“…Recently CD23, also known as Fcε receptor II, was reported to be a functional receptor of AIMP1 in monocytes (21). Because CD23 is also a marker of mature B cells, we hypothesized that AIMP1 activates B cells via CD23.…”
Section: Discussionmentioning
confidence: 96%